Екологізація діяльності ІТ-компаній через впровадження "зелених" технологій - Сакун, Антоніна Олегівна; Калашник, Т. В.; Пащенко, П. С. (ГО "Міжнародна наукова гільдія", 2026)
The rapid development of the IT industry is accompanied by increasing energy consumption and a growing environmental impact associated with data processing and digital infrastructure. This study examines the possibilities of greening the activities of IT companies through the implementation of green technologies and energy-efficient solutions. Particular attention is given to improving the energy efficiency of data centers, optimizing cooling systems, and integrating renewable energy sources. The implementation of such approaches can reduce energy consumption, lower carbon emissions, and contribute to the sustainable development of the IT sector.
Keywords: екологія; екологізація; ІТ-компанії; зелені технології; цифрові технології; концепція Green IT